2016
DOI: 10.1080/13510002.2015.1107312
|View full text |Cite
|
Sign up to set email alerts
|

Redox status of the testes and sperm of rats following exposure to 2,5-hexanedione

Abstract: 2,5-HD exposure impaired testicular function and sperm characteristics by disruption of the antioxidant systems and consequently, increased oxidative stress in the treated rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Glutathione S ‐transferase has dual functions in antioxidant defense and xenobiotic detoxication, loss of the enzyme activity could lead to increased susceptibility of testis to tebuconazole toxicity and render testis a major target organ. Along this line, decrease of testicular glutathione S ‐transferase activity has been reported in male rats treated with reproductive toxicants triazine and 2,5‐hexanedione and functionalized multi‐walled carbon nanotubes …”
Section: Discussionmentioning
confidence: 85%
“…Glutathione S ‐transferase has dual functions in antioxidant defense and xenobiotic detoxication, loss of the enzyme activity could lead to increased susceptibility of testis to tebuconazole toxicity and render testis a major target organ. Along this line, decrease of testicular glutathione S ‐transferase activity has been reported in male rats treated with reproductive toxicants triazine and 2,5‐hexanedione and functionalized multi‐walled carbon nanotubes …”
Section: Discussionmentioning
confidence: 85%
“…25,26 Testicular weight is an important marker of male reproductive toxicity whereas the RTW is an established indicator of degenerative changes including swelling, atrophy or hypertrophy. 47 The decrease in the absolute and RTWs observed in mice exposed to DSS alone and SZ alone indicates testicular atrophy mediated by DSS-induced colitis and SZ, respectively. Our observation on the reduction in testes weight is in contrast to previous observations in acute testicular effect of SZ administration in Sprague Dawley rats for 14 days.…”
Section: Discussionmentioning
confidence: 97%
“…Data obtained from this study indicated that GSC treatment in rats did not elicit changes on absolute weights and organosomatic indices of both testis and epididymis. Since the gross weight and organosomatic indices of the testes mirror the condition of the organ following exposure to xenobiotics, the lack of discernible effect of GSC on the germ cells could be inferred from the data [ 23 ].…”
Section: Discussionmentioning
confidence: 99%